(untitled) (Gestión y Gerencia, 2023)
The research proposes the use of cryptocurrencies as a new alternative within the means of payment in small and medium-sized enterprises (SMEs) in Barquisimeto, Lara State. It consisted of a quantitative exploration and a sample of 15 commercial SMEs was analyzed, to whom a questionnaire of 24 questions and an interview with a sample of 117 clients were applied. Both instruments were validated under expert judgment. The variables and indicators were analyzed with descriptive statistical techniques, through tables and graphs. It is concluded that cryptocurrencies represent a means of payment that speeds up and facilitates economic transactions between two parties and increases post-transaction liquidity within SMEs, and without the intervention of a third agent. Likewise, the strength of this medium lies in the stability of the currency after its convertibility, as well as its annual profitability.